1997
DOI: 10.3109/10641969709083208
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acid Receptors in the Paraventricular Hypothalamic Nucleus Mediate Pressor Response Induced by Carotid Body Chemoreceptor Stimulation in Rats

Abstract: k u m o r i D e p a r t m e n t of Pharmacology, Showa College of P h a r m a c e u t i c a l Sciences, Machida, Tokyo 194, J a p a n Key words: Excitatory a m i n o acid receptors; Carotid body; Chemoreceptor; P a r a v e n t r i c u l a r h y p o t h a l a m i c nucleus; Kynurenate; Blood p r e s s u r e ABSTRACT I n u r e t h a n e -a n e s t h e t i z e d r a t s w i t h spinal transection, antagonists of excitatory a m i n o acid receptors, P 2 p u r i n o c e p t o r s a n d a d r e n o c e p t o r s w e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
1
33
0
2
Order By: Relevance
“…In contrast, intracerebroventricular administration of UII increased CBF. The cortical hemodynamic effect could be associated with the UII activation of different brain areas involved in cardiovascular regulation (Martin and Haywood, 1992;Kubo et al, 1997;Comer et al, 1998;Haywood et al, 2001). In fact, local injection of UII into the paraventricular nucleus, arcuate nucleus, and noradrenergic cells in the lower part of the medulla induces cardiovascular effects (Lu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intracerebroventricular administration of UII increased CBF. The cortical hemodynamic effect could be associated with the UII activation of different brain areas involved in cardiovascular regulation (Martin and Haywood, 1992;Kubo et al, 1997;Comer et al, 1998;Haywood et al, 2001). In fact, local injection of UII into the paraventricular nucleus, arcuate nucleus, and noradrenergic cells in the lower part of the medulla induces cardiovascular effects (Lu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To further support this notion, Kubo et al (1997) reported that the excitatory amino acid antagonist kynurenate injected into the PVN inhibited the chemoreceptor reflex-induced pressor response in anesthetized rats. Later, Olivan et al (2001) demonstrated bilateral electrolytic lesion of the PVN in conscious rats produced a significant reduction in the magnitude and duration of the pressor response induced by chemoreflex activation, suggesting that the PVN is involved in the regulation of cardiovascular responses to CB chemoreflex activation.…”
Section: Cb Chemoreflex At the Level Of The Paraventricular Nucleus Omentioning
confidence: 99%
“…Several studies have identified central neural structures involved in the sympathoexcitatory component of chemoreflexes; however, most have focused on the pons and the medulla (Guyenet 2000), which are the primary projection areas of chemosensitive afferents and the primary sites for respiratory and sympathetic integration. Apart from these areas of the brain, other studies suggest an involvement of the hypothalamus in modulating the respiratory and cardiovascular responses to hypoxia and hypercapnia (Horn & Waldrop 1994,Kubo et al 1997,Olivan et al 2001. In particular, hypoxia and hypercapnia stimulate neurons in various hypothalamic nuclei, including the PVN (Berquin et al 2000).…”
Section: Cb Chemoreflex At the Level Of The Paraventricular Nucleus Omentioning
confidence: 99%
“…The following doses of the drugs were used: Kyn, 0.15 to 5 nmol/50 nL; AP5, 0.16 to 1.4 nmol/50 nL; CNQX, 0.22 to 1.8 nmol/50 nL; and gabazine, 0.3 to 10 nmol/50 nL. The microinjection doses for Kyn, 15,27 AP5, 15 CNQX, 29 and gabazine 30,31 were selected from previous studies and tested in the pilot experiments.…”
Section: Pvn Microinjectionsmentioning
confidence: 99%